Polyether amide synergists

By using polyether amides with multiple alkylene oxide units to interact with silica particles, the coating stability problem caused by increased load of silica particles is solved, and efficient low shear viscosity and rapid viscosity rebound are achieved, improving The sag behavior of the paint.

CN119192563APending Publication Date: 2024-12-27EVONIK OPERATIONS GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410841497.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-19
Filing Date
2024-06-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art often leads to an increase in the loading of silica particles when increasing the thixotropic effect of silica rheology modifiers, resulting in poor in-tank stability of the coating and affects the final coating properties such as gloss and transparency, and viscosity back The elastic speed is not related to the low shear viscosity and cannot effectively prevent sagging.

Method used

Polyetheramides with three or more alkylene oxide units are used as organic polymers, in conjunction with silica particles, enhance low shear viscosity and provide rapid after high shear Viscosity rebounds to improve sag behavior.

Benefits of technology

By reducing the load of silica particles, the stability of the coating is avoided, while the low shear viscosity of the coating is improved and the rapid viscosity rebound after high shear is improved, which significantly improves the sag behavior of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004914476080000121
    Figure BDA0004914476080000121
  • Figure BDA0004914476080000131
    Figure BDA0004914476080000131
  • Figure BDA0004914476080000141
    Figure BDA0004914476080000141
Patent Text Reader

Abstract

Disclosed is an organic polymer of structure (AmBn)-(C) x wherein A is a polycarboxylic acid having two or more carboxyl groups, B is a polyamine having two or more amine groups, m > = 1, n > = 1, and x = 2-6; c has the structure F (D) y wherein F is a urethane, amide and / or ester function, D is a C2 to C18 moiety having at least one primary, secondary and / or tertiary hydroxyl group, and y = 1-6, characterized in that AmBn comprises 3 or more alkylene oxide units and 1 or more ethylene oxide units.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to organic polymers capable of enhancing the thixotropic effect of a class of silica-based rheology modifiers, the production of such polymers and their use in solvent-borne coating formulations.

[0002] Such polymers capable of increasing the thixotropic effect of silica-based rheology modifiers are also referred to as synergists, since they are used together with silica-based rheology modifiers.

[0003] Silica particles are used as rheology modifiers in coating formulations. They are effective in improving low shear viscosity and are widely used to improve the anti-sagging property of coatings during the application process. This effect is caused by non-covalent interactions between silica particles and with other ingredients in the coating formulation, especially through hydrogen bonding interactions. Non-covalent interactions are destroyed under high shear conditions, but rebound when the shear force is removed or reduced. This feature is also called thixotropic effect, which is necessary for the ease of coating application that occurs when high shear and sagging are reduced after the application process. Sagging reduction depends on the rapid viscosity rebound when the shear force is removed. Generally, this effect can be enhanced by increasing the amount of silica particles, i.e., higher low shear viscosity and faster viscosity rebound. However, higher loadings of silica particles often lead to poor stability in the can, as shown by the sedimentation of silica particles, and adversely affect the final coating properties, such as gloss and transparency. In addition, the speed of viscosity rebound after high shear may not be very relevant to high low shear viscosity. A fast rebound time is desired to improve the sagging behavior of the applied coating composition.

[0004] US 4,857,111 discloses hydroxyl functional polycarboxylic acid amides as synergists to improve the thixotropic effect of silica particles in solvent-based coating formulations. The disclosed structure may be a polymer having 2 to 18 hydroxyl groups connected to the main chain by amide bonds. The main chain may be a polyamide having 2, 4, 6 or 8 amide groups, or the main chain may be a polyether. However, after high shear stress, such as by brushing or spraying, the rebound back to the original viscosity is not fast enough to effectively prevent sagging.

[0005] US2010 0323112A1 discloses the use of hydroxyl functional amide compounds, in combination with silica and 1 wt% to 7 wt% of the total coating formulation of (i) a volatile organic liquid having an evaporation rate less than or equal to 0.1 and (ii) in which the hydroxyl functional amide compound is insoluble, to achieve anti-sagging properties. The disclosed structure may be a polymer having 2 to 18 hydroxyl groups connected to the backbone by amide bonds. The backbone comprises a polyamide chain or a polyether having 2, 4, 6 or 8 amide groups. In addition to the required volatile organic liquid limiting the choice of solvents that can be used in the coating composition, similar to US 4,857,111 with insoluble hydroxyl functional amide compounds, the anti-sagging behavior is still unsatisfactory.

[0006] US 9,822,234 discloses an additive for increasing thixotropy, which is produced by the condensation of (a) a polyalkylene polyamine which can form at least one imidazoline and / or tetrahydropyrimidine unit and has at least two primary amino groups or at least one primary amino group and at least one secondary amino group and (b) a dimer fatty acid, a trimer fatty acid or a mixture thereof, or a reaction product of at least two dimer fatty acids or trimer fatty acids or a mixture thereof and at least one polyamine having at least two primary amino groups. Although the proposed additive can increase thixotropy compared to without the addition of the additive, the additive can still improve the sagging behavior.

[0007] WO 2021 / 185898 A1 discloses a rheology control agent comprising silicon dioxide and polyethyleneimine having a molecular weight in the range of 40,000 to 300,000 g / mol, which polyethyleneimine is further reacted with an epoxide compound. However, polyethyleneimine is an expensive additive with very limited commercial availability. In addition, the production process involves the handling of toxic substances.

[0008] WO 2021 / 008954 A1 discloses a composition comprising an organic modified silica and an organic compound having an amine and a hydroxyl group. The organic compound is produced by an epoxide ring-opening reaction of an amine mixture containing 2-amino-2-hydroxymethyl-1,3-propanediol (TRIS) and a glycidyl ether. The proposed compound requires an amine equivalent of less than 5000, which is undesirable in terms of environmental toxicity.

[0009] US 2007 / 225451 discloses biuret compounds as rheology control additives.

[0010] It is therefore an object of the present invention to provide an organic polymer that acts synergistically with silica particles as a rheology modifier for coating compositions to improve the rheological properties of coating compositions and that can at least reduce the disadvantages of prior art molecules used with silica particles to modify the rheology of coating compositions. It is another object of the present invention that the organic polymer can increase the low shear viscosity of solvent-borne coating compositions in combination with silica particles and that imparts a rapid viscosity rebound after the coating composition is exposed to high shear, thereby enhancing the sagging behavior of the coating composition.

[0011] This object is achieved by an organic polymer of the following structure I:

[0012] (A m B n )-(C) x (I)

[0013] wherein A is a polycarboxylic acid having two or more carboxyl groups or anhydrides, esters or acyl halides thereof and mixtures thereof,

[0014] B is a polyamine having two or more amine groups,

[0015] m, n and x are molar ratios, wherein m≥1, n≥1, and x=2-6;

[0016] C has the following structure II:

[0017] F(D) y (II)

[0018] wherein F is a urethane, amide and / or ester functional group, and D is a C2 to C4 hydroxyl group having at least one primary, secondary and / or tertiary hydroxyl group. 18 part, and y = 1-6,

[0019] It is characterized by m B n is a polyetheramide comprising three or more oxyalkylene units, and at least one of the oxyalkylene units is an ethylene oxide unit. The oxyalkylene units may optionally be substituted oxyalkylene units and are derived from a glycidyl ether functional group.

[0020] The organic polymers according to the present invention are used together with silica particles as rheology modifiers for solvent-borne coating compositions. It has surprisingly been found that the organic polymers according to the present invention in combination with silica particles increase the low shear viscosity of solvent-borne coating compositions and impart a rapid viscosity rebound after the coating composition is exposed to high shear, thereby enhancing the sagging behavior of the coating composition.

[0021] The organic polymers according to the present invention allow avoiding the necessity to increase the silica loading of the coating composition in order to improve the rheology of the coating composition, thereby preventing the negative effects of higher silica loadings, which are poor in-can stability due to settling of silica particles, and adversely affecting the final coating properties, such as gloss and transparency.

[0022] Component A is a polycarboxylic acid or anhydride, ester or halide thereof and mixtures thereof. As used herein, the term "polycarboxylic acid" refers to an organic acid containing two or more carboxyl groups and preferably no other functional groups. Most preferably, the carboxyl group is connected to a hydrocarbon portion.

[0023] The polycarboxylic acid (A) and the polyamine (B) are linked by an amide bond. The amide bond is formed by condensation of the carboxyl group of the polycarboxylic acid (A) and the amine group of the polyamine (B). m B n ) is a polyetheramide.

[0024] According to the present invention, a polyetheramide (A) comprising at least one ethylene oxide unit and a hydroxyl functional group is required. m B n ) to achieve the desired properties. In addition to amides, hydroxyl functional groups can also be linked to polyetheramides via ester and urethane bonds. m B n ) is formed by reacting a polycarboxylic acid (A) and a polyamine (B) in a m / n molar ratio. A polyether segment comprising at least one ethylene oxide unit is incorporated into the polyetheramide by using a polycarboxylic acid having a polyether segment and / or a polyamine having a polyether segment. The resulting polyetheramide is then reacted with x mol of an amine-reactive precursor or a carboxylic acid-reactive precursor to obtain (A m B n )-(C) x , wherein C comprises a hydroxyl-containing moiety (D) and an ester, amide and / or urethane bond (F).

[0025] D is preferably an alcohol or an alcohol and an amine substituted C2 to C 18 hydrocarbon.

[0026] The organic polymers according to the present invention do not require the use of volatile organic liquids in the coating composition to achieve the desired anti-sagging properties as required by US 2010 / 0323112 A1.

[0027] In order to address the drawbacks caused by the limited amount of silica that can be used in solvent-borne coating compositions, organic polymers that can form non-covalent interactions with silica particles in order to further improve the rheological properties have been proposed in the prior art.

[0028] Such prior art polymers typically have a hydrophobic polyamide backbone, which results in partial solubility in the coating system and components that interact with the silica particles, such as hydroxyl groups (US 4,857,111) or imidazoline and / or tetrahydropyrimidine units (US 9,822,234). The partial solubility caused by the hydrophobic polyamide can result in viscosity enhancement. However, as shown in the examples below, there is still room for better performance in terms of viscosity rebound after removal of high shear.

[0029] It was found quite unexpectedly that the organic polymers according to the invention constituting the polyetheramides are able to enhance the low shear viscosity of solvent-borne coating formulations containing silica and at the same time impart a rapid viscosity rebound after the coating composition has been exposed to high shear. The incorporation of polyether segments, especially polyether segments containing polar ethylene oxide units, should increase the solubility of the polymer in solvent-borne coating compositions and thus reduce the effectiveness of the polymer for enhancing the rheological properties of the coating. However, surprisingly it could be shown that the organic polymers according to the invention constituting the polyetheramides are able to enhance the low shear viscosity of solvent-borne coating compositions containing silica and impart a rapid viscosity rebound after the coating composition has been exposed to high shear, thereby enhancing the sagging behavior.

[0030] A m B n The term alkylene oxide here refers to the reaction products of alkylene oxides.

[0031] The subscripts m, n, x and y are preferably integers.

[0032] In the case of a structure (A m B n )-(C) x In the organic polymer according to the invention, component A is preferably an aliphatic or aromatic polycarboxylic acid having two or three carboxyl groups or anhydrides, esters or halides thereof and mixtures thereof. The proviso is always that component A or component B or both comprise three or more oxyalkylene units and at least one of the oxyalkylene units in A or B is an ethylene oxide unit.

[0033] A can be a dimer fatty acid or a trimer fatty acid or a mixture of the two. Such a dimer fatty acid or trimer fatty acid is preferably produced from an unsaturated fatty acid having 12 to 22 carbon atoms, more preferably from tall oil having 18 carbon atoms. The dimer fatty acid or trimer fatty acid may be optionally hydrogenated. The condition is always that A is formed from components A and B. m B n Three or more oxyalkylene units are included, and at least one of the oxyalkylene units is an ethylene oxide unit.

[0034] More preferably, in the organic polymer according to the present invention, A is an aliphatic or aromatic polycarboxylic acid having two carboxyl groups. Most preferably, A is selected from oxalic acid, diethyl oxalate, oxalyl chloride, succinic acid, succinic anhydride, octyl succinic anhydride, decyl succinic anhydride and dodecyl succinic anhydride, fumaric acid, diethyl fumarate, maleic acid, maleic anhydride, diethyl maleate, glutaric acid, glutaric anhydride, adipic acid, adipic anhydride, diglycolic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, acid), dimer fatty acids, mesaconic acid, malonic acid, itaconic acid, itaconic anhydride, citraconic acid, citraconic anhydride, hexahydrophthalic acid, tetrahydrophthalic acid, dihydrophthalic acid, methylhexahydrophthalic acid and methyltetrahydrophthalic acid, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, dihydrophthalic anhydride, methylhexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic acid, phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, dimethyl terephthalate, naphthalene dicarboxylic acid, naphthalene anhydride, 3,6,9-trioxaundecanedioic acid (3,6,9-trioxaundecanedioic acid acid), poly(ethylene glycol) bis(carboxymethyl) ether, α,ω-bis[2-[(3-carboxy-1-oxopropyl)amino]ethyl]-poly(ethylene glycol), and mixtures thereof.

[0035] In another preferred embodiment of the organic polymer according to the present invention, A is an aliphatic or aromatic polycarboxylic acid having three carboxyl groups or an anhydride, ester or halide thereof and mixtures thereof. If A is an aliphatic or aromatic polycarboxylic acid having three carboxyl groups, more preferably, A is selected from tricarballylic acid, butanetricarboxylic acid, trimesic acid, trimellitic acid, trimellitic anhydride, trimerized fatty acid (trimer acid), 3-arm poly(ethylene glycol)carboxylic acid; tris[2-[(3-carboxy-1-oxopropyl)amino]ethyl]-poly(ethylene glycol) and mixtures thereof.

[0036] In the case of a structure (A m B n )-(C) x In the organic polymer according to the invention, component B is preferably an aliphatic or aromatic polyamine having 2 to 6 amine groups, provided that component A or component B or both comprise three or more oxyalkylene units and at least one of the oxyalkylene units in A or B is an ethylene oxide unit.

[0037] More preferably, B is an aliphatic or aromatic polyamine selected from ethylenediamine, propylenediamine, hexamethylenediamine, methylpentamethylenediamine, isophoronediamine, cyclohexanediamine, xylenediamine, 4,4-diaminodicyclohexylmethane, octamethylenediamine, 1,12-dodecanediamine, dimer diamine, trioxatridecanediamine, polyether diamine or triamine, poly(oxyethylene) diamine, poly(oxypropylene) diamine, poly(oxyethylene-oxypropylene) diamine, glyceryl poly(oxypropylene) triamine, diethylenetriamine, triaminononane, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, bis-hexamethylenetriamine, bis-aminopropylpiperazine and mixtures thereof. Most preferably, B is a polyetherdiamine having one or more ethylene oxide repeating units.

[0038] Components A and B react to form A m B n The choice of A and B must make A m B n The required alkylene oxide units and ethylene oxide units according to the invention are present.

[0039] The organic polymer component C according to the invention consists of urethane or amide and / or ester functional groups (F) and a portion D, wherein D contains at least one primary and / or secondary and / or tertiary hydroxyl group. It has the structure F(D) y . F acts as D and A m B n C is a chain end segment of the organic polymer according to the present invention.

[0040] C can be prepared by reacting an amine-reactive precursor with a m B n ) reacts to form (A) having at least one primary, secondary or tertiary hydroxyl group in part C. m B n )-(C) x To obtain.

[0041] Preferably, the amine-reactive precursor is selected from lactic acid, glycolic acid, dimethylolpropionic acid, salicylic acid, malic acid, citric acid, isocitric acid, mandelic acid, hydroxymalonic acid, tartaric acid, hydroxybutyric acid, hydroxyvaleric acid, hydroxycaproic acid, hydroxystearic acid, ricinoleic acid, caprolactone, valerolactone, butyrolactone, lactide or a mixture thereof. When the precursor is a hydroxy acid, lactone or lactide, it reacts with A m B n In this case, F is an amide function and D is a C2 to C4 hydroxyl group having at least one primary, secondary and / or tertiary hydroxyl group as required according to the invention. 18 part.

[0042] In another preferred embodiment according to the present invention, the amine reactive precursor is a carbonate, which is preferably selected from ethylene carbonate, propylene carbonate and glycerol carbonate. When the precursor is a carbonate, it reacts with the amine reactive precursor present in A m B n The amine in the amine forms a urethane, in which case F is a urethane functional group and D is a C2 to C3 moiety having at least one primary, secondary and / or tertiary hydroxyl group as required according to the invention. 18 part.

[0043] In another preferred embodiment of the present invention, C is obtained by reacting a carboxylic acid reactive precursor with a m B n ) reacts to form (A m B n )-(C) x The precursor is preferably an amino alcohol. When the precursor is an amino alcohol, it reacts with the precursor present in A m B n The carboxylic acid groups in the amino alcohol form amides or esters. Then F is an amide and / or ester functional group. The amino alcohol is selected so that D is a C2 to C3 hydroxyl group having at least one primary hydroxyl group, secondary hydroxyl group and / or tertiary hydroxyl group as required according to the present invention. 18 part.

[0044] More preferably, the carboxylic acid reactive precursor is selected from diethanolamine, tris(hydroxymethyl)aminomethane and epoxy-amine adducts having at least one secondary amine and mixtures thereof.

[0045] The thus formed part C can be further extended by reacting the hydroxyl groups present in C with lactone or lactide. This extension preferably does not change the number of hydroxyl groups in part C.

[0046] The reaction of the polycarboxylic acid A and the polyamine B is a polycondensation reaction to form an alternating sequence of A and B along the polyetheramide backbone.

[0047] A preferred embodiment of the present invention is an organic polymer of structure I:

[0048] (A m B n )-(C) x (I)

[0049] wherein A is a dimer fatty acid, B is a polyamine having two or more amine groups, m≥1, n≥1, and x=2-6;

[0050] C has the following structure II:

[0051] F(D)y (II)

[0052] wherein F is a urethane, amide and / or ester functional group, and D is a C2 to C4 hydroxyl group having at least one primary, secondary and / or tertiary hydroxyl group. 18 part, and y = 1-6,

[0053] The condition is A m B n Three or more oxyalkylene units are included, and at least one of the oxyalkylene units is an ethylene oxide unit.

[0054] Another preferred embodiment of the present invention is an organic polymer of structure I:

[0055] (A m B n )-(C) x (I)

[0056] wherein A is a polycarboxylic acid having two or more carboxyl groups, B is a polyether diamine or a polyether triamine, m≥1, n≥1, and x=2-6;

[0057] C has the following structure II:

[0058] F(D) y (II)

[0059] wherein F is a urethane, amide and / or ester functional group, and D is a C2 to C4 hydroxyl group having at least one primary, secondary and / or tertiary hydroxyl group. 18 part, and y = 1-6,

[0060] The condition is A m B n Three or more oxyalkylene units are included, and at least one of the oxyalkylene units is an ethylene oxide unit.

[0061] Another preferred embodiment of the present invention is an organic polymer of structure I:

[0062] (A m B n )-(C) x (I)

[0063] wherein A is a dimer fatty acid, B is a polyether diamine or a polyether triamine, m≥1, n≥1, and x=2-6;

[0064] C has the following structure II:

[0065] F(D) y (II)

[0066] wherein F is a urethane, amide and / or ester functional group, and D is a C2 to C4 hydroxyl group having at least one primary, secondary and / or tertiary hydroxyl group. 18 part, and y = 1-6,

[0067] The condition is A m B n Three or more oxyalkylene units are included, and at least one of the oxyalkylene units is an ethylene oxide unit.

[0068] The present invention also encompasses a method for producing an organic polymer according to the present invention. This method comprises the steps of: reacting a polycarboxylic acid A and a polyamine B at a temperature of 140° C. to 200° C. for 4 to 8 hours to form A m B n , and then make the A formed thereby m B n The reaction is then continued with the precursor of C as described above at a temperature of 140 to 180°C for another 4 to 8 hours, or if the precursor of C is a carbonate, at a temperature of 100 to 150°C for another 4 to 8 hours.

[0069] Most advantageously, the organic polymer according to the invention is added to a solventborne coating composition. Thus, the invention also encompasses a solventborne coating composition comprising an organic polymer according to the invention, a solventborne resin system and hydrophilic or hydrophobic silica particles. The solventborne coating composition may be a clear coating or may additionally contain pigments, binders, fillers and other additives.

[0070] The solvent-based coating composition according to the present invention preferably comprises:

[0071] 0.1 wt% to 10 wt% of an organic polymer according to any one of claims 1 to 12,

[0072] 60wt%-98wt% solvent-based resin system, and

[0073] 0.1wt%-10wt% hydrophilic or hydrophobic silica particles,

[0074] 0wt%-30wt% of pigments, binders, fillers,

[0075] Provided that the sum of all components equals 100 wt%.

[0076] Those skilled in the art can select from a variety of solvents of the solvent-based resin system according to the components of the resin and the organic polymer of the present invention. Suitable solvents can be ketones, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone; aromatic hydrocarbons, such as toluene, xylene, styrene, A100, P100; mineral spirits; ethyl acetate, butyl acetate, propylene glycol methyl ether acetate; glycol ethers, such as diethylene glycol dimethyl ether, dipropylene glycol methyl ether; dibasic esters and alcohols. Preferably, the solvent is selected from aromatic hydrocarbons and ketones.

[0077] The resin of the solvent-based resin system may be selected from acrylic resins, polyurethane resins, polyester resins, epoxy resins, polyaspartic acid resins, phenolic resins and alkyd resins. Preferably, the resin of the solvent-based resin system is selected from acrylic resins, polyurethane resins, polyester resins or epoxy resins.

[0078] A method of coating a surface also forms part of the present invention. Such a method comprises the steps of providing a solventborne coating composition as described above, comprising an organic polymer according to the present invention and hydrophilic or hydrophobic silica particles; applying the solventborne coating composition at least partially to a surface; and drying or curing the coating composition. Application to a surface may be carried out by any means known to those skilled in the art, for example by dipping, brushing or spraying. Example

[0079] Example 1: Synthesis of synergist S1

[0080] C36 dimer acid (component A) and a polyether diamine (component B) having 9 ethylene oxide units and a molecular weight of about 600 g / mol are mixed and reacted at a temperature of 150 to 200° C. for 4-8 hours. The condensed water is removed. When the amine value of the reaction mixture is ≤5 mgKOH / g, the reaction mixture is then cooled to 60-90° C. and diethanolamine (DEA, a precursor of component C) is added. The mixture is heated to 140 to 180° C. for 4-8 hours. Then, when the acid value of the reaction mixture drops to ≤10 mgKOH / g, the reaction mixture is cooled to 60-90° C. and a solvent mixture of xylene and P100 (naphtha, a light aromatic fraction) and isobutanol is added. The molar ratios of the reactants used are shown in Table 1. Solvents are used to reduce the viscosity of the material.

[0081] The acid value was determined according to ASTM D1639-90. The amine value was determined according to ASTM D2074-07 (2019). The molecular weight M was determined according to ASTM D5296-19 n 、M w . M n is the number average molecular weight, and M wis the weight average molecular weight. Then, the non-volatile content (NV) was determined according to ASTM D2369-20.

[0082] Example 2: Synthesis of synergist S2

[0083] Synergist S2 was obtained in a similar manner as shown in Example 1, but the molar ratios of the reactants were different, as shown in Table 1.

[0084] Example 3: Synthesis of synergist S3

[0085] Synergist S3 was obtained in a similar manner to that shown in Example 1, wherein the reactant ratios were different and a polyetherdiamine having 13 ethylene oxide units was used as component B, as shown in Table 1.

[0086] Example 4: Synthesis of synergist S4

[0087] Synergist S4 was obtained in a similar manner to that shown in Example 1, wherein the reactant ratios were different and a polyetherdiamine without ethylene oxide units was used as component B, as shown in Table 1. S4 served as comparative example.

[0088] Example 5: Synthesis of synergist S5

[0089] Synergist S5 was obtained in a similar manner as shown in Example 1, with different reactant ratios and tris(hydroxymethyl)aminomethane (TRIS) as a precursor to C, as shown in Table 1.

[0090] Example 6: Synthesis of synergist S6

[0091] Synergist S6 was obtained in a similar manner to that shown in Example 1, wherein the reactant ratios were different and a polyetherdiamine having 39 ethylene oxide units was used as component B and tris(hydroxymethyl)aminomethane (TRIS) as precursor for C.

[0092] Example 7: Synthesis of synergist S7

[0093] Synergist S7 was obtained in a similar manner as shown in Example 1, wherein the reactant ratios were different and a polyetherdiamine without ethylene oxide units was used as component B and tris(hydroxymethyl)aminomethane (TRIS) as precursor for C, as shown in Table 1. S7 served as a comparative example.

[0094] Example 8: Synthesis of synergist S8

[0095] C36 dimer acid (component A) and polyether diamine (component B) having 9 ethylene oxide units and a molecular weight of about 600 g / mol were mixed and reacted at a temperature of 150 to 200° C. for 4-8 hours. The condensed water was removed. When the acid value of the reaction mixture dropped to ≤6 mgKOH / g, the reaction mixture was then cooled to 60-90° C. and glycerol carbonate (GC, a precursor of component C) was added. The mixture was heated to 130 to 160° C. for a further 4-8 hours until the amine value was reduced to ≤12 mgKOH / g. The reaction mixture was then cooled to 50° C. and diluted with xylene. The molar ratios of the reactants used are shown in Table 1.

[0096] Example 9: Synthesis of synergist S9

[0097] Synergist S9 was obtained in a similar manner to that shown in Example 8, with the only difference that a polyetherdiamine without ethylene oxide units was used as component B, as shown in Table 1. S9 served as comparative example.

[0098] Example 10: Synthesis of synergist S10

[0099] Synergist S10 was obtained in a similar manner as shown in Example 8, but the molar ratios of the reactants were different, as shown in Table 1.

[0100] Example 11: Synthesis of synergist S11

[0101] Synergist S11 was obtained in a similar manner to that shown in Example 8, wherein the reactant ratios were different and a polyetherdiamine having 39 ethylene oxide units was used as component B, as shown in Table 1.

[0102] Example 12: Synthesis of synergist S12

[0103] Synergist S12 was obtained in a similar manner as shown in Example 8, wherein the reactant ratios were different and a polyetherdiamine having 39 ethylene oxide units was used as component B, as shown in Table 1.

[0104] Example 13: Synthesis of synergist S13

[0105] Synergist S13 was obtained in a similar manner as shown in Example 8, wherein the reactant ratios were different and C42 trimer acid was used as component A and a polyether diamine having 39 ethylene oxide units as component B, as shown in Table 1.

[0106]

[0107] Table 1: Composition and properties of synergists S1 to S13 prepared as described in Examples 1 to 13.

[0108] *m, n and x represent the obtained m B n )-(C) x The molar ratio of A, B and C in the synergists S1 to S13 is

[0109] Dimer acid: C36 dimer acid

[0110] Trimer acid: C42 trimer acid

[0111] PEA1: polyether diamine with 9 ethylene oxide units, molecular weight about 600 g / mol

[0112] PEA2: polyether diamine with 13 ethylene oxide units, molecular weight about 900 g / mol

[0113] PEA3: polyether diamine without ethylene oxide units, molecular weight of about 230 g / mol

[0114] PEA4: polyether diamine with 39 ethylene oxide units, molecular weight about 2000 g / mol

[0115] DEA: Diethanolamine (Sigma-Aldrich)

[0116] TRIS: Tris(hydroxymethyl)aminomethane (Sigma-Aldrich)

[0117] GC: Glyceryl Carbonate (Huntsman)

[0118] Example 14: Preparation of solvent-based unsaturated polyester coating composition

[0119] As shown in Table 2 below, solvent-based unsaturated polyester coating composition AI was prepared by mixing unsaturated polyester resin and silica particles at ambient temperature. The unsaturated polyester resin was dispersed in a high shear dispersion apparatus (Dispermat) with a cowl blade at 200-400 s. -1 The mixture was ground at a shear rate of 100 μm for at least 10 min to achieve a grind below 45 μm. The remaining ingredients were then added in the order listed in Table 2 and the mixture was ground at 30-60 s. -1 Mix for another 5 minutes at a shear rate or with a high speed mixer until the composition is uniform. Keep the composition in a glass jar with a tight lid and let it sit until rheological testing the next day.

[0120]

[0121] Table 2. Examples of solvent-based unsaturated polyester-based formulations for synergist evaluation

[0122] Unsaturated polyester resin is an unsaturated polyester resin (AOC resin) derived from isophthalic acid. The specific surface area is 175-225m 2 / g of hydrophilic fumed silica (Evonik).

[0123] Synergist S14 is a commercially available synergist polymer consisting of a solution of a polyhydroxycarboxamide containing no oxyalkylene units.

[0124] Example 15: Rheological Testing of Solvent-Based Unsaturated Polyester Coating Compositions

[0125] Synergists S1, S2, S3, S4, S8, S9, S10 and S14 were tested in solvent-borne unsaturated polyester coating compositions B to I containing silica particles. The key performance indicators for the synergists are the low shear viscosity of the coating composition and the time required for sufficient viscosity rebound after shear stress.

[0126] The solvent-based unsaturated polyester coating composition A contained only silica particles but no synergist polymer.

[0127] The rheology of coating composition AI was tested with a rotational rheometer (Anton Paar 302). The rheological test was performed on the second day (note as day 1) after the preparation and overnight standing of the formulation and after 14 days of storage at 25°C. The measurement was performed using a standard parallel plate spindle with a diameter of 25 mm. The spindle was brought to the formulation sample immediately after sample loading, with a gap of 1 mm, and the temperature control of the rheometer plate was set at 25°C.

[0128] To evaluate thixotropy, a four-step shear test was developed. First, all samples were subjected to a low shear rate (0.01 s -1 ) for 120 s to reach steady state to replicate the behavior of the sample at near rest, and then the shear rate was increased from 0.01s -1 Gradually increase to 50s -1 (Logarithmic curve) to replicate the decomposition of the sample structure. In the third step, it was subjected to a constant high shear rate (50s -1 ) for 60 seconds and reach another steady state, then return to the same low shear rate (0.01s -1 ) to recover and rebuild the structure. The shear stress versus shear rate is recorded and the viscosity (η) function over time is calculated. The time taken for the sample viscosity to recover to 90% of its initial viscosity is used as a measure of thixotropy, and a shorter recovery time indicates a faster structural reconstruction within the coating composition.

[0129]

[0130] Table 3: Viscosity of coating compositions A to I after 1 day and after 14 days and the corresponding time to recover to 90% of the viscosity after the four-step shear test.

[0131] In 0.01s -1 The initial viscosity (Pa.s) at day 1 and day 14 was measured at 40 °C. The recovery time is the time taken for the coating sample to recover to 90% of its initial viscosity after the above four-step shear test.

[0132] For the unsaturated polyester coating composition used, an initial viscosity of 250 Pa.s or less indicates poor sagging behavior. An initial viscosity in the region of 300 Pa.s or more indicates good sagging behavior.

[0133] If the initial viscosity on day 1 is less than 250 Pa.s, the coating composition is not suitable for commercial use even if it increases slightly after storage for 14 days.

[0134] Table 3 shows the initial viscosities of coating compositions A to I after 1 day and 14 days of storage and the time taken for these compositions to recover 90% of their initial viscosity after a four-step shear test.

[0135] Coating composition A served as a control and included only silica particles as a rheology modifier but no additional synergist to improve the rheological behavior. The low initial viscosity of 145 Pa.s indicated poor sagging behavior.

[0136] The coating composition B including the commercially available synergist polymer S14 showed a high initial viscosity of 400 Pa.s after 1 day and 570 Pa.s after 14 days, which indicates good sagging behavior. However, for a coating to be suitable for use, not only a high initial viscosity is required, but also a fast recovery time to rebound to the initial viscosity after exposure to shear stress. The recovery times of the coating composition B after the shear test were 57 seconds and 60 seconds, respectively. Such a long recovery time will result in poor sagging behavior when the coating is applied to the surface.

[0137] The coating composition C comprising the synergist S1 according to the invention also exhibits a high initial viscosity of 386 Pa.s after 1 day and 757 Pa.s after 14 days. In addition to the high initial viscosity, the coating composition C exhibits a much shorter recovery time than the coating compositions A and B. The recovery times of the coating composition C after the shear test were 15 seconds and 17 seconds, respectively. The combination of high initial viscosity and short recovery time will result in good sagging behavior when the coating is applied to a surface.

[0138] The coating composition D comprising the synergist S2 according to the invention also exhibits a high initial viscosity of 338 Pa.s after 1 day and 654 Pa.s after 14 days. In addition to the high initial viscosity, the coating composition D also exhibits a much shorter recovery time than the coating compositions A and B. The recovery times of the coating composition D after the shear test were 13 seconds and 7 seconds, respectively. The combination of high initial viscosity and short recovery time will result in good sagging behavior when the coating is applied to a surface.

[0139] The coating composition E comprising the synergist S3 according to the invention also exhibits a high initial viscosity of 416 Pa.s after 1 day and 811 Pa.s after 14 days. In addition to the high initial viscosity, the coating composition E also exhibits a much shorter recovery time than the coating compositions A and B. The recovery times of the coating composition E after the shear test were 20 seconds and 21 seconds, respectively. The combination of high initial viscosity and short recovery time will result in good sagging behavior when the coating is applied to a surface.

[0140] Coating composition F including synergist S4 is a comparative example. Synergist S4 was produced using a polyether diamine without ethylene oxide units as component B and therefore does not fall within the scope of the present invention. The thickening effect of this synergist is unsatisfactory. The initial viscosity of coating composition F was only 205 Pa.s after 1 day and 313 Pa.s after 14 days. Despite the short recovery time, the sagging behavior was poor due to the low viscosity.

[0141] The coating composition G comprising the synergist S8 according to the invention exhibits a high initial viscosity of 431 Pa.s after 1 day and 645 Pa.s after 14 days. In addition to the high initial viscosity, the coating composition G also exhibits a much shorter recovery time than the coating compositions A and B. The recovery times of the coating composition G after the shear test are 4 seconds and 8 seconds respectively. The combination of high initial viscosity and short recovery time will result in good sag behaviour when the coating is applied to a surface.

[0142] The coating composition H including the synergist S9 is a comparative example. The synergist S9 was produced using a polyether diamine without ethylene oxide units as component B and therefore does not belong to the scope of the present invention. The thickening effect of the synergist is unsatisfactory. The initial viscosity of the coating composition H was only 212 Pa.s after 1 day and 279 Pa.s after 14 days. Despite the short recovery time, the sagging behavior was poor due to the low viscosity.

[0143] Similar to coating compositions C, D, E and G, coating composition I including synergist S10 according to the present invention also exhibits a high initial viscosity of 848 Pa.s after 1 day and 753 Pa.s after 14 days. In addition to the high initial viscosity, coating composition I also exhibits a much shorter recovery time than coating compositions A and B. The recovery times of coating composition I after the shear test were 10 seconds and 7 seconds, respectively. The combination of high initial viscosity and short recovery time will result in good sagging behavior when the coating is applied to a surface.

[0144] Example 16: Preparation of solvent-based acrylic polyol 2KPU coating composition

[0145] Solvent-based acrylic polyol 2KPU coating compositions J, K and L were prepared by mixing acrylic polyol with butyl acetate and silica particles at ambient temperature (as shown in Table 4 below). The mixture was mixed for 5 minutes at a shear rate of 2500 rpm on a high shear dispersing device and further ground for 60 min with a Skandex disperser in the presence of 200 g of 3 mm glass beads as a grinding aid to achieve a grind below 20 μm. The glass beads were filtered and the remaining ingredients except the hardener were added in the order listed in Table 4 and mixed for another 5 minutes at a shear rate of 500 rpm with a paddle stirrer. The composition was kept in a glass jar with a sealing lid and allowed to stand until the hardener was added the next day. The hardener was added to the composition at a shear rate of 1000 rpm and mixed for 1 minute at 23°C. Rheological testing was performed after 10 minutes.

[0146]

[0147] Table 4. Examples of solventborne acrylic polyol 2KPU coating composition formulations for synergist evaluation.

[0148] Acrylic polyol resins (Allnex) are hydroxyl functional resins designed for crosslinking with polyisocyanate hardeners. The polyisocyanate hardener (Evonik) reacts with the acrylic polyol over time to form a thermosetting coating. Use a specific surface area of ​​175-225m 2 / g of hydrophilic fumed silica (Evonik).

[0149] Synergist S14 is a commercially available synergist polymer consisting of a solution of a polyhydroxycarboxamide containing no oxyalkylene units.

[0150] Example 17: Rheological test of solvent-based acrylic polyol 2KPU coating composition

[0151] Synergists S1 and S14 were tested in solventborne acrylic polyol 2KPU coating compositions K to L containing silica particles. The key performance indicators for the synergists are the low shear viscosity of the coating composition and the time required for sufficient viscosity rebound after shear stress.

[0152] The solvent-based acrylic polyol 2KPU coating composition J contained only silica particles but no synergist polymer.

[0153] The rheology of coating compositions J, K and L was tested with a rotational rheometer (Anton Paar 302). The rheological test was performed 10 minutes after the addition of the polyisocyanate hardener. The measurement was performed using a standard parallel plate rotor with a diameter of 25 mm. Immediately after sample loading, the rotor was brought to the formulation sample with a gap of 1 mm and the temperature control of the rheometer plate was set at 23°C. At a low shear rate (0.1 s -1 ) to measure the initial viscosity of the sample for 60 seconds. Then, apply 500s -1 A high shear rate of 120 s was applied to replicate the decomposition of the sample structure, followed by a 0.5 s -1 A lower shear rate is used for the sample to recover and rebuild structure. The shear stress is recorded versus the shear rate and the viscosity (η) function over time is calculated. The time taken for the sample viscosity to recover to 90% of its initial viscosity is used as a measure of thixotropy, and a shorter recovery time indicates a faster structural rebuilding within the coating composition.

[0154] Coating composition Initial viscosity (mPa.s) Viscosity after recovery 30s (mPa.s) J 200 200 K 4000 400 L 3600 280

[0155] Table 5: At 0.1s -1 The initial viscosity of coating compositions J to L measured at 0.5 s -1 The corresponding recovered viscosity after 30 s of recovery was measured below.

[0156] Coating composition J served as a control and included only silica particles as a rheology modifier but no additional synergist to improve the rheological behavior. The low initial viscosity of 200 mPa.s indicated poor sagging behavior.

[0157] The coating composition L including the commercially available synergist polymer S14 exhibits a high initial viscosity of 3600 mPa.s. However, for such a coating to be suitable for use, not only a high initial viscosity is required, but also a fast viscosity recovery after exposure to shear stress. 30 s after the shear test, the viscosity of the coating composition L is 280 mPa.s, which is only slightly higher than that of the control J, and thus still exhibits poor sagging properties.

[0158] The coating composition K comprising the synergist S1 according to the invention also shows a high initial viscosity of 4000 mPa.s. In addition to the high initial viscosity, the coating composition K exhibits a stronger viscosity recovery than the coating compositions J and L. 30 s after the shear test, the viscosity of the coating composition K is 400 mPa.s. The combination of high initial viscosity and fast viscosity recovery leads to good sagging behavior when the coating is applied to a surface.

Claims

1. An organic polymer of the following structure I: (A m B n )-(C) x (I) wherein A is a polycarboxylic acid having two or more carboxyl groups or anhydrides, esters or acyl halides thereof and mixtures thereof, B is a polyamine having two or more amine groups, m, n and x are molar ratios, wherein m≥1, n≥1, and x=2-6; C has the following structure II: F(D) y (II) wherein F is a urethane, amide and / or ester functional group, and D is a C2 to C4 hydroxyl group having at least one primary, secondary and / or tertiary hydroxyl group. 18 part, and y = 1-6, Features A m B n It is a polyetheramide comprising 3 or more oxyalkylene units and 1 or more ethylene oxide units.

2. The organic polymer according to claim 1, characterized in that A is an aliphatic or aromatic polycarboxylic acid having two or three carboxyl groups, or anhydrides, esters or halides thereof, and mixtures thereof.

3. The organic polymer according to claim 2, characterized in that A is an aliphatic or aromatic polycarboxylic acid having two carboxyl groups selected from oxalic acid, diethyl oxalate, oxalyl chloride, succinic acid, succinic anhydride, octyl succinic anhydride, decyl succinic anhydride and dodecyl succinic anhydride, fumaric acid, diethyl fumarate, maleic acid, maleic anhydride, diethyl maleate, glutaric acid, glutaric anhydride, adipic acid, adipic anhydride, diglycolic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, dimerized fatty acids, mesaconic acid, malonic acid, itaconic acid, itaconic anhydride, citraconic acid, citraconic anhydride, hexahydrophthalic acid, tetrahydrophthalic acid, dihydrophthalic acid Acid, methylhexahydrophthalic acid and methyltetrahydrophthalic acid, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, dihydrophthalic anhydride, methylhexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic acid, phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, dimethyl terephthalate, naphthalenedicarboxylic acid, naphthalene dicarboxylic acid, naphthalene anhydride, 3,6,9-trioxaundecanedioic acid, poly(ethylene glycol) bis(carboxymethyl) ether, α,ω-bis[2-[(3-carboxy-1-oxopropyl)amino]ethyl]-poly(ethylene glycol) and mixtures thereof.

4. The organic polymer according to claim 2, characterized in that A is an aliphatic or aromatic polycarboxylic acid having three carboxyl groups or anhydrides, esters or halides thereof and mixtures thereof.

5. The organic polymer according to claim 4, characterized in that A is selected from the group consisting of tricarballylic acid, butanetricarboxylic acid, trimesic acid, trimellitic acid, trimellitic anhydride, trimerized fatty acid (trimer acid) and mixtures thereof.

6. The organic polymer according to claim 1, characterized in that B is an aliphatic or aromatic polyamine having 2 to 6 amine groups.

7. The organic polymer according to claim 6, characterized in that B is an aliphatic or aromatic polyamine selected from ethylenediamine, propylenediamine, hexamethylenediamine, methylpentamethylenediamine, isophoronediamine, cyclohexanediamine, xylenediamine, 4,4-diaminodicyclohexylmethane, octamethylenediamine, 1,12-dodecanediamine, dimer diamine, trioxatridecanediamine, polyether diamines or triamines, poly(oxyethylene)diamine, poly(oxypropylene)diamine, poly(oxyethylene-oxypropylene)diamine, glyceryl poly(oxypropylene)triamine, diethylenetriamine, triaminononane, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, bis-hexamethylenetriamine, bis-aminopropylpiperazine, and mixtures thereof.

8. The organic polymer according to claim 1, characterized in that C is obtained by reacting an amine-reactive precursor with a m B n ) reacts to form (A) having at least one primary hydroxyl group, secondary hydroxyl group or tertiary hydroxyl group m B n )-(C) x To obtain.

9. The organic polymer according to claim 8, characterized in that The amine-reactive precursor is selected from lactic acid, glycolic acid, dimethylolpropionic acid, salicylic acid, malic acid, citric acid, isocitric acid, mandelic acid, hydroxymalonic acid, tartaric acid, hydroxybutyric acid, hydroxyvaleric acid, hydroxycaproic acid, hydroxystearic acid, ricinoleic acid, caprolactone, valerolactone, butyrolactone, lactide or a mixture thereof.

10. The organic polymer according to claim 8, characterized in that The amine-reactive precursor is selected from ethylene carbonate, propylene carbonate and glycerol carbonate.

11. The organic polymer according to claim 1, characterized in that C is obtained by reacting a carboxylic acid reactive precursor with a m B n ) in which the carboxyl groups react to form (A m B n )-(C) x The precursor has at least one primary hydroxyl group, a secondary hydroxyl group or a tertiary hydroxyl group.

12. The organic polymer according to claim 11, characterized in that The carboxylic acid reactive precursor is selected from the group consisting of diethanolamine, tris(hydroxymethyl)aminomethane, epoxy-amine adducts having at least one secondary amine, and mixtures thereof.

13. A method for producing an organic polymer according to any one of claims 1 to 12, comprising the steps of: A and B are reacted at a temperature of 140°C to 220°C for 4-8 hours to form A m B n , and then make the A formed thereby m B n The precursor of C is reacted at a temperature of 140 to 180°C for another 4 to 8 hours, or if the precursor of C is a carbonate, at a temperature of 100 to 150°C for another 4 to 8 hours.

14. A solvent-based coating composition comprising the organic polymer according to any one of claims 1 to 12, a solvent-based resin system and hydrophilic or hydrophobic silica particles.

15. The solvent-based coating composition according to claim 14, characterized in that The solvent is selected from aromatic hydrocarbons and ketones.

16. The solvent-based coating composition according to claim 14 or 15, characterized in that The resin is selected from acrylic resin, polyurethane resin, polyester resin and epoxy resin.

17. A method for coating a surface comprising the steps of: Providing a coating composition according to claim 14, 15 or 16; applying the coating at least partially to a surface; and drying or curing the coating composition.